2014
DOI: 10.1111/jocn.12539
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetes patients' experiences of, and need for, social support after attending a structured education programme: a qualitative longitudinal investigation

Abstract: Health professionals including diabetes specialist nurses and dietitians should explore: patients' access to and preferences for social support; how patients might be encouraged to capitalise on social support postcourse; and new ways to inform/educate people within patients' social networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 39 publications
1
28
0
1
Order By: Relevance
“…Indeed, when they were interviewed after their courses and 6 months later, patients in both arms reported very similar benefits and improvements to their lives. For example, patients in both arms -like other DAFNE graduates who have taken part in longitudinal qualitative research 154 -reported a renewed enthusiasm for managing their diabetes after attending their courses and being more open to discussing aspects of their condition and self-management practices with family and friends. As a consequence, patients also discussed being more open to seeking and accepting support from these family members and friends.…”
Section: Results Of the Psychosocial Evaluationmentioning
confidence: 99%
“…Indeed, when they were interviewed after their courses and 6 months later, patients in both arms reported very similar benefits and improvements to their lives. For example, patients in both arms -like other DAFNE graduates who have taken part in longitudinal qualitative research 154 -reported a renewed enthusiasm for managing their diabetes after attending their courses and being more open to discussing aspects of their condition and self-management practices with family and friends. As a consequence, patients also discussed being more open to seeking and accepting support from these family members and friends.…”
Section: Results Of the Psychosocial Evaluationmentioning
confidence: 99%
“…However, some patients also reported that their parents struggled to provide relevant support because the DAFNE approach ran counter to historic and out-of-date ways in which they had been taught to manage their child's diabetes. 81 Educators also recognised that patients often wanted one-to-one follow-up support from DAFNE-trained health professionals to be available as and when needed but also described the difficulties that this would incur for their already busy work lives. Aware of constraints on their time, several educators suggested establishing regular DAFNE-specific drop-in clinics that patients could attend without an appointment to seek support and clarification on course-related topics.…”
Section: Qualitative and Quantitative Evaluation Of The Dafne Intervementioning
confidence: 99%
“…In addition, patients reported an increased use of family support networks after their course, largely because of their own and others' increased enthusiasm for diabetes management. 81 To support patients effectively, members of these networks could also benefit from instruction on course-recommended approaches to managing (mild) hypoglycaemia. 78 Also, given that family/partners are often involved in food preparation, they might also benefit from training in CP counting.…”
Section: Qualitative and Quantitative Evaluation Of The Dafne Intervementioning
confidence: 99%
“…The key focus of the group is to promote learning and understanding of a condition with a view to supporting someone self-manage. The group normally ends when the formal education is completed although on-going support may be required [33]. The education is predominantly health care profession led although the method of delivery of education is very variable.…”
Section: Recruitment and Attendancementioning
confidence: 99%
“…Hence, there may be a place for education being offered to a cultural group, even although all attendees might not actually benefit from the specific education. However, the extended group would provide the much needed social support normally required to embed changes in self-management [33]. Hence the group provides the social support that is needed [16].…”
Section: Recruitment and Attendancementioning
confidence: 99%